Comparison of SARS-CoV-2 test positivity in NCAA Division I student athletes vs nonathletes at 12 institutions - Schultz, E. A.; Kussman, A.; Jerome, A.; Abrams, G. D.; Hwang, C. E. (JAMA network Open, 2022)
Importance: The COVID-19 pandemic initially led to the abrupt shutdown of collegiate athletics until guidelines were established for a safe return to play for student athletes. Currently, no literature exists that examines the difference in SARS-CoV-2 test positivity between student athletes and nonathletes at universities across the country. Objective: To identify the difference in risk of COVID-19 infection between student athlete and nonathlete student populations and evaluate the hypothesis that student athletes may display increased SARS-CoV-2 test positivity associated with increased travel, competition, and testing compared with nonathletes at their respective universities. Design, Setting, and Participants: In this cross-sectional analysis, a search of publicly available official university COVID-19 dashboards and press releases was performed for all 65 Power 5 National Collegiate Athletic Association (NCAA) Division I institutions during the 2020 to 2021 academic year. Data were analyzed at the conclusion of the academic year. Schools that released at least 4 months of testing data, including the fall 2020 football season, for student athletes and nonathlete students were included in the analysis. Power 5 NCAA Division I student athletes and their nonathlete student counterparts were included in the analysis. Exposure: Designation as a varsity student athlete. Main Outcomes and Measures: The main outcome was SARS-CoV-2 test positivity for student athletes and nonathlete students at the included institutions for the 2020 to 2021 academic year, measured as a relative risk for student athletes. Results: Among 12 schools with sufficient data available included in the final analysis, 555372 student athlete tests and 3482845 nonathlete student tests were performed. There were 9 schools with decreased test positivity in student athletes compared with nonathlete students (University of Arkansas: 0.01% vs 3.52%; University of Minnesota: 0.63% vs 5.96%; Penn State University: 0.74% vs 6.58%; Clemson University: 0.40% vs 1.88%; University of Louisville: 0.75% vs 3.05%; Purdue University: 0.79% vs 2.97%; University of Michigan: 0.40% vs 1.12%; University of Illinois: 0.17% vs 0.40%; University of Virginia: 0.64% vs 1.04%) (P < .001 for each). The median (range) test positivity in these 9 schools was 0.46% (0.01%-0.79%) for student athletes and 1.04% (0.40%-6.58%) for nonathlete students. In 1 school, test positivity was increased in the student athlete group (Stanford University: 0.20% vs 0.05%; P < .001). Overall, there were 2425 positive tests (0.44%) among student athletes and 30567 positive tests (0.88%) among nonathlete students, for a relative risk of 0.50 (95% CI, 0.48-0.52; P < .001). There was no statistically significant difference in student athlete test positivity between included schools; however, test positivity among nonathlete students varied considerably between institutions, ranging from 133 of 271862 tests (0.05%) at Stanford University to 2129 of 32336 tests (6.58%) at Penn State University. Conclusions and Relevance: This study found that in the setting of SARS-CoV-2 transmission mitigation protocols implemented by the NCAA, participation in intercollegiate athletics was not associated with increased SARS-CoV-2 test positivity. This finding suggests that collegiate athletics may be held without an associated increased risk of infection among student athletes.